The Influence of Environmental Sustainability Orientations on organizational Performance: A Review - Mishra, Anjay Kumar; Thakur, Ritesh Kumar; Dhakal, Sitaram (Journal of Productive Discourse, 2024)
This comprehensive review addresses a critical research gap concerning the relationship between Entrepreneurial Orientation (EO), Environmental Sustainability Orientation (ESO), and organizational performance. The study advocates for future research to delve into this uncharted territory, providing valuable insights for organizations and policymakers to promote entrepreneurship and sustainable business practices. It suggests a deeper examination of EO, specifically Innovativeness, Proactiveness, and Risk-Taking, as independent variables, alongside organizational performance as the dependent variable. The review emphasizes the pivotal mediating role of ESO, highlighting its strategic significance in differentiating firms and enhancing performance. It affirms the positive influence of EO on ESO, subsequently improving organizational performance. The review stresses the managerial implications of integrating EO dimensions into strategies for a competitive advantage, along with the importance of embracing ESO for reputation enhancement and cost reduction through eco-friendly practices. The study encourages future researchers to explore additional EO variables and utilize diverse data analysis tools to enhance understanding of the intersection of entrepreneurial and sustainability orientations.